ANALISIS PERBEDAAN RASIO KEUANGAN PT BANK MANDIRI TBK DAN PT BANK SYARIAH MANDIRI TBK PERIODE 2010-2014 (IAIN Tulungagung, 2016)
The purpose of this study was to determine the Bank’s fnancial performance for the Islamic and Conventional Banks each fnancial ratio over a period of 5 years for the years 2010 to 2014. Financial ratios used in this study consisted of CAR, NPL, NIM, ROE, BOPO. As for the purpose of this study was to examine differences in fnancial ratios of PT Bank Mandiri Tbk and PT Bank Syariah Mandiri Tbk period 2010-2014. This study uses a quantitative approach to the type of comparative research. The data used in this research is time series data. Based on the criteria determined sample, the obtained two research groups are represented by the Islamic Bank PT Bank Syariah Mandiri Tbk and Bank Conventional represented by PT Bank Mandiri Tbk. The analytical tool used to prove the hypothesis in this study was independent sample t-test. The results of the study with the tools SPSS version 16.0 concluded that the average (mean) ratio of NIM and ROE PT Bank Syariah Mandiri Tbk better performance than PT Bank Mandiri Tbk, while the average yield (mean) CAR, NPL and BOPO PT Bank Mandiri Tbk showed better performance than PT Bank Syariah Mandiri Tbk. While the views of the results of hypothesis testing with different test (independent sample t-test) showed a signifcant difference in the CAR, NPL, ROE and BOPO. As for the ratio of NIM is not a signifcant difference.Keyword: CAR, NPL, NIM, ROE, BOPO